Investigating the challenges in revenue collection process and the development of a computerised solution: The case study of AMA property rate collection - Tahiru, Fati (2014)
A thesis submitted to the Department of Computer Science, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Philosophy in Information Technology,